STRATEGI PENGEMBANGAN SUMBERDAYA MANUSIA DALAM MENINGKATKAN KUALITAS PELAYANAN PENANGANAN PERKARA EKONOMI SYARIAH DI PENGADILAN AGAMA BADUNG - Moh. Irham Maulana (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
This paper describes the strategy of human resource development (judge) in increasing the quality of case handling of syariah economic peayanan in the judicial Institutions of religion. The focus of the study explained how development, strategy planning, training and development, evaluation and oversight of resources of economic justice of the Sharia Religious Court in Badung made using field studies are qualitative. The results of this study that in doing development resources in the judge did with several stages starting from the planning, training and development, performance appraisal, and controlling